Proteomic Analysis Reveals the Protective Effects of Selenomethionine Against Liver Oxidative Injury in Piglets - Kai Zhang; Shuhui Yan; Junhong Miao; Wen Li; Zhenxu Li (Animals, 2025)
This study investigated the protective effects of high selenomethionine (SeMet) supplementation on liver injury caused by oxidative stress in piglets and explored the underlying mechanisms. A total of 18 piglets were randomly assigned to three groups, with six replicates in each group. The control (CON) and diquat (DQ) groups were fed a basal diet supplemented with 0.3 mg Se/kg Se, while the SeMet group received a basal diet supplemented with 1.0 mg Se/kg. The results indicated that SeMet supplementation significantly improved growth performance and increased the serum and liver activities of antioxidant enzymes. Additionally, it reduced the serum and liver levels of malondialdehyde and protein carbonyls in piglets exposed to DQ. Selenoprotein transcriptome analysis showed that the mRNA levels of five selenoprotein genes (GPX1/3, DIO2, and SELENOF/M/W) were significantly upregulated by dietary SeMet supplementation in the liver of DQ-challenged piglets. Proteomic analysis revealed that a total of 3614 proteins were identified in the liver of piglets. Among them, 85 differentially expressed proteins (DEPs) were identified between the CON and DQ groups, 58 DEPs were observed between the DQ and SeMet groups, and 113 DEPs were identified between the CON and SeMet groups. KEGG analysis indicated that most of the DEPs observed among the three groups were involved in fatty acid metabolism, glycolysis/gluconeogenesis, and the PPAR signaling pathway. Together, these results indicate that dietary supplementation with supernutritional SeMet alleviates the negative effects of the DQ challenge on growth performance and liver injury in piglets. This effect is associated with increased antioxidant capacity, enhanced expression of certain selenoprotein genes, and the regulation of fatty acid metabolism.